Evaluation of different initial feed on growth performance, intestinal morphology and microbiota diversity, immunity response, and disease resistance of pacific short-finned glass eel, Anguilla bicolor pacifica - Yen-Ting Lin; Hsiang-Yi Hsu; Yu-San Han (Aquaculture Reports)
Currently, aquaculture fishermen predominantly use bloodworms (Chironomus spp. or Tubifex sp.) or eel powder as initial feed for the pacific short-finned glass eel, Anguilla bicolor pacifica. However, bloodworms thrive in waters rich in organic matter, making them prone to carrying pathogens into aquaculture systems, particularly Edwardsiella tarda, a severe bacterial pathogen for all Anguilla species. Therefore, this research explored the use of an artificial paste feed as the initial feed for pacific short-finned glass eels in the recirculating aquaculture system (RAS), evaluating growth performance, immune gene expression, disease resistance, and intestinal morphology and microbiota diversity across different initial feeds for glass eels. The paste feed demonstrated similar attractiveness and palatability to pacific short-finned glass eels as bloodworms, both of which were superior to eel powder. There were no significant differences in growth performance between the paste feed and bloodworm groups, but the survival rate in the paste feed group was significantly higher than in the bloodworm group. In terms of intestinal morphology, only the paste feed group showed no inflammation or abnormalities and had significantly longer villi. Moreover, the relative expression of superoxide dismutase (SOD) and peroxidase (POD) were significantly higher in the paste feed group compared with the bloodworm and powder groups, resulting in the best survival rate following an E. tarda challenge test. Additionally, the significantly lower expression of interleukin-6 (IL-6) and heat shock protein 70 (HSP70) indicates reduced stress and inflammation in the paste feed group. The biodiversity index indicated that the paste feed group showed a significantly lower alpha diversity than the bloodworm and powder groups, and harmful pathogens (such as Aeromonas) were not detected in the intestines. These results indicate that paste feed is safer and more efficient than bloodworms and eel powder for pacific short-finned glass eels.